Moderate Genetic Diversity and Demographic Reduction in the Threatened Giant Anteater, Myrmecophaga tridactyla - Barragán-Ruiz, Carmen Elena; Silva-Santos, Rosane; Saranholi, Bruno H.; Desbiez, Arnaud L. J.; Galetti, Pedro Manoel (Frontiers in Genetics, 2021)
In general, large mammal species with high specialized feeding behavior and solitary habits are expected to suffer genetic consequences from habitat loss and fragmentation. To test this hypothesis, we analyzed the genetic diversity distribution of the threatened giant anteater inhabiting a human-modified landscape. We used ten microsatellite loci to assess the genetic diversity and population structure of 107 giant anteaters sampled in the Brazilian central-western region. No genetic population structuring was observed in this region suggesting no gene flow restriction within the studied area. On the other hand, the moderate level of genetic diversity (Ho = 0.54), recent bottleneck detected and inbreeding (Fis, 0.13 p ≤ 0.05) signatures suggest potential impacts on the genetic variation of this Xenarthra. Additionally, a past demographic reduction was also suggested. Thus, considering the increased human-promoted impacts across the entire distribution giant anteater area, our results can illustrate the potential effects of these disturbances on the genetic variation, allowing us to infer the long-term conservation of this emblematic species.